Candida infections in solid organ transplantation: Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice - Aslam, Saima; Rotstein, Coleman; Practice, the AST Infectious Disease Community of (Clinical Transplantation, 2019)
These updated guidelines from the American Society of Transplantation Infectious Diseases Community of Practice provide recommendations for the diagnosis and management of Candida infections in solid organ transplant recipients. Candida infections manifest primarily as candidemia and invasive candidiasis and cause considerable morbidity and mortality. Early diagnosis and initiation of treatment are necessary to reduce mortality. For both candidemia and invasive candidiasis, an echinocandin is recommended for initial therapy. However, early transition to oral therapy is encouraged when patients are stable and the organism is susceptible. Candida prophylaxis should be targeted for high-risk patients in liver, small bowel, and pancreas transplant recipients. Future research should address which patient groups may benefit most from preventative antifungal therapy strategies.
Keywords: antifungal; fungal; infection and infectious; infection and infectious agents

Cryptococcosis in solid organ transplantation—Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice - Baddley, John W.; Forrest, Graeme N.; Practice, the AST Infectious Diseases Community of (Clinical Transplantation, 2019)
These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention, and management of cryptococcosis in the pre- and post-transplant period. The current update now includes a discussion of cryptococcosis, which is the third most common invasive fungal infection in SOT recipients. Infection often occurs a year after transplantation; however, early infections occur and donor-derived infections have been described within 3 months after transplant. There are two main species that cause infection, Cryptococcus neoformans and C gattii. Clinical onset may be insidious, but headaches, fevers, and mental status changes should warrant diagnostic testing. The lateral flow cryptococcal antigen assay is now the preferred test from serum and cerebrospinal fluid due to its rapidity, accuracy, and cost. A lumbar puncture with measurement of opening pressure is recommended for patients with suspected or proven cryptococcosis. Lipid amphotericin B plus 5-flucytosine is used as initial treatment of meningitis, disseminated infection, and moderate-to-severe pulmonary infection, followed by fluconazole as consolidation therapy. Fluconazole is effective for mild-to-moderate pulmonary infection. Immunosuppression reduction as part of management may lead to immune reconstitution syndrome that may resemble active disease.
Keywords: antibiotic; antifungal; complication; fungal; infection and infectious agents; infectious

Pneumocystis jiroveci in solid organ transplantation: Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice - Fishman, Jay A.; Gans, Hayley; Practice, the AST Infectious Diseases Community of (Clinical Transplantation, 2019)
These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention, and management of Pneumocystis jiroveci fungal infection transplant recipients. Pneumonia (PJP) may develop via airborne transmission or reactivation of prior infection. Nosocomial clusters of infection have been described among transplant recipients. PJP should not occur during prophylaxis with trimethoprim-sulfamethoxazole (TMP-SMX). Without prophylaxis, PJP risk is greatest in the first 6 months after organ transplantation but may develop later. Risk factors include low lymphocyte counts, cytomegalovirus infection (CMV), hypogammaglobulinemia, treated graft rejection or corticosteroids, and advancing patient age (>65). Presentation typically includes fever, dyspnea with hypoxemia, and cough. Chest radiographic patterns generally reveal diffuse interstitial processes best seen by CT scans. Patients generally have PO2 < 60 mm Hg, elevated serum lactic dehydrogenase (LDH), and elevated serum (1 → 3) β-d-glucan assay. Specific diagnosis uses respiratory specimens with direct immunofluorescent staining; invasive procedures may be required. Quantitative PCR is a useful adjunct to diagnosis. TMP-SMX is the drug of choice for therapy; drug allergy should be documented before resorting to alternative therapies. Adjunctive corticosteroids may be useful early. Routine PJP prophylaxis is recommended for at least 6-12 months post–transplant, preferably with TMP-SMX.
Keywords: antimicrobial; corticosteroid therapy; fungal; infection and infectious agents; pneumocystis jirovecii; pneumocystis pneumonia

Invasive Aspergillosis in solid-organ transplant recipients: Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice - Husain, Shahid; Camargo, Jose F. (Clinical Transplantation, 2019)
These updated AST-IDCOP guidelines provide information on epidemiology, diagnosis, and management of Aspergillus after organ transplantation. Aspergillus is the most common invasive mold infection in solid-organ transplant (SOT) recipients, and it is the most common invasive fungal infection among lung transplant recipients. Time from transplant to diagnosis of invasive aspergillosis (IA) is variable, but most cases present within the first year post-transplant, with shortest time to onset among liver and heart transplant recipients. The overall 12-week mortality of IA in SOT exceeds 20%; prognosis is worse among those with central nervous system involvement or disseminated disease. Bronchoalveolar lavage galactomannan is preferred for the diagnosis of IA in lung and non-lung transplant recipients, in combination with other diagnostic modalities (eg, chest CT scan, culture). Voriconazole remains the drug of choice to treat IA, with isavuconazole and lipid formulations of amphotericin B regarded as alternative agents. The role of combination antifungals for primary therapy of IA remains controversial. Either universal prophylaxis or preemptive therapy is recommended in lung transplant recipients, whereas targeted prophylaxis is favored in liver and heart transplant recipients. In these guidelines, we also discuss newer antifungals and diagnostic tests, antifungal susceptibility testing, and special patient populations.

Endemic fungal infections in solid organ transplant recipients—Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice - Miller, Rachel; Assi, Maha; Practice, the AST Infectious Diseases Community of (Clinical Transplantation, 2019)
These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention and management of blastomycosis, histoplasmosis, and coccidioidomycosis in the pre- and post-transplant period. Though each of these endemic fungal infections has unique epidemiology and clinical manifestations, they all share a predilection for primary pulmonary infection and may cause disseminated infection, particularly in immunocompromised hosts. Culture remains the gold standard for definitive diagnosis, but more rapid diagnosis may be achieved with direct visualization of organisms from clinical specimens and antigen-based enzyme immunoassay assays. Serology is of limited utility in transplant recipients. The mainstay of treatment for severe infections remains liposomal amphotericin followed by a step-down azole therapy. Cases of mild to moderate severity with no CNS involvement may be treated with azole therapy alone. The newer generation azoles provide additional treatment options, but supported currently with limited clinical efficacy data. Azole therapy in transplant recipients presents a unique challenge owing to the drug-drug interactions with immunosuppressant agents. Therapeutic drug monitoring of azole levels is an essential component of effective and safe therapy. Infection prevention centers around minimizing epidemiological exposures, early clinical recognition, and azole prophylaxis in selected individuals.
Keywords: Antifungal; antifungal; azole; blastomycosis; coccidioidomycosis; fungal infection; histoplasmosis